Anthropological Mechanisms of Self-Management of Personality Behavior - Dzhamalova, Bika B.; Magomedov, Guseyn B.; Amirkhanov, Amirkhan A.; Ramazanova, Pati K.; Suleymanov, Bigruzi B. (International Review of Management and Marketing, 2016)
Security of personality is not only a set of specific measures to ensure its protection from various dangers, but a condition of being protected, which is based on the ability to self-manage one's own behavior. The aim of the article is to identify the anthropological mechanisms to self-manage the behavior of the individual. The leading approach to the study is the anthropological approach that considers the personality as a product of human existence; the aggregate's bearer of socially significant features and mental characteristics, established during ontogeny and determining the behavior of the individual, as a conscious entity of activities and social relations. The article defines the essence and structure of psychological security of a person; clarifies and describes cognitive, emotional, behavioral self-regulation mechanisms to promote the effectiveness of coping behavior of the individual; identifies and justifies mechanisms of information-psychological self-protection that are manifested in the unconscious, subconscious and conscious levels. The paper submissions can be useful for managers and teachers of educational institutions; employees of the centers of advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff. Keywords: Self-Management, Anthropological Mechanisms, Psychological Safety, Coping Behavior. JEL Classifications: I21, I25, I28